Flow - Fry, Ben; Reas, Casey (Processing, 2014)
The programs we’ve seen so far run each line of code in sequence from top to bottom. They run the first line, then the second, then the third, and so on. The program stops when the last line is run. It’s often beneficial to change this order—sometimes skipping lines or repeating lines many times to create movement. Although the lines of code in a program are always positioned in an order from top to bottom on the page, this doesn’t necessarily define the order in which each line is run. This order is called theflowof the program.